2007
DOI: 10.1002/cm.20241
|View full text |Cite
|
Sign up to set email alerts
|

A FAK/Src chimera with gain‐of‐function properties promotes formation of large peripheral adhesions associated with dynamic actin assembly

Abstract: Formation of a complex between the tyrosine kinases FAK and Src is a key integrin-mediated signaling event implicated in cell motility, survival, and proliferation. Past studies indicate that FAK functions in the complex primarily as a "scaffold," acting to recruit and activate Src within cell/matrix adhesions. To study the cellular impact of FAK-associated Src signaling we developed a novel gainof-function approach that involves expressing a chimeric protein with the FAK kinase domain replaced by the Src kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…Previous study has documented the critical role of actin microfilaments in the internalisation process of S. aureus (Ellington et al, 1999). Considering that FAK and Src family kinases are main signalling required to stabilise the actin microfilaments (Frame, 2004; Siesser et al, 2008), our study raises the possibility of FAK/Src/microfilaments system in initiating the internalisation of S. aureus by osteoblasts.…”
Section: Discussionmentioning
confidence: 77%
“…Previous study has documented the critical role of actin microfilaments in the internalisation process of S. aureus (Ellington et al, 1999). Considering that FAK and Src family kinases are main signalling required to stabilise the actin microfilaments (Frame, 2004; Siesser et al, 2008), our study raises the possibility of FAK/Src/microfilaments system in initiating the internalisation of S. aureus by osteoblasts.…”
Section: Discussionmentioning
confidence: 77%
“…TGF‐β1 can induce the activation of Src by autophosphorylation of the tyrosine 416 . In the presence of active TGF‐β1, during a murine study of bleomycin‐induced lung fibrosis, epithelial integrin and focal adhesion kinases up‐regulated Src activity and Src inhibition attenuated EMT, which is a potential source of myofibroblasts accumulation in fibrotic lungs . Moreover, previous studies have demonstrated that oral administration of 60 and 100 mg/kg of nintedanib is sufficient to inhibit FGFRs, VEGFRs, Lck, Src and Flt‐3 in mice .…”
Section: Discussionmentioning
confidence: 99%
“…However, accumulating evidence suggests that a much more elaborate mechanism is required to fine-tune the activity of FAK because it is involved in multiple steps of the cell motility cycle (18), including adhesion assembly, actin remodeling, and adhesion turnover, which is why simple loss/gain-offunction studies often lead to seemingly contradictory results in the literature. For instance, an increase in FAK activity has been reported to reduce motility, stabilize adhesion, and promote stress fiber assembly (19), possibly via RhoA activation (20); however, on the other hand, FAK deficiency in a number of cell types also led to reduced motility, with impaired adhesion turnover and hyperactivated Rho-Rho associated coiled-coil containing protein kinase (Rho-ROCK) signaling (21,22). To ensure timely activation of a suitable downstream signaling pathway, it is likely that an efficient mechanism is in place to regulate this multifunctional molecule.…”
Section: Discussionmentioning
confidence: 99%